A cabazitaxel liposome for increased solubility, enhanced antitumor effect and reduced systemic toxicity - Xiaoyi Yin; Lihua Luo; Wei Li; Jie Yang; Chunqi Zhu; Mengshi Jiang; Bing qin; Xiaoling Yuan; Hang Yin; Yichao Lu; Yongzhong Du; Dawei Chen; et al. (Elsevier, 2019)
The potential side effects of cabazitaxel (CBZ) in the field of cancer treatment have become a great limitation to its further clinical application. Liposomal delivery is a well-established approach to increase the therapeutic index of hydrophobic drugs. In this study, a PEG-modified liposome was developed for efficiently encapsulating CBZ, thus enhancing its specific tumor inhibition effect and reducing the systemic toxicity. It was found that the loading efficiency of CBZ into the liposome could be improved with the increase of lipophilic materials, as it could be over 80% under the weight ratio of 20:1 (total lipid: CBZ). The diameter of CBZ loaded liposome (CBZ@Lipo) was ∼100 nm. And the liposome suspending in aqueous medium was stable at 4 °C for at least one month, according to the change of its size distribution. The killing ability of CBZ@Lipo to cancer cells was significantly lower comparing to that of CBZ solution, which could be attributed to the slow release of CBZ from the liposomes. However, CBZ@Lipo could induce an obvious apoptosis of the cancer cells at low concentration. Furthermore, CBZ@Lipo exhibited an expressively enhanced tumor growth inhibition effect comparing to CBZ solution. More importantly, CBZ@Lipo showed an obviously higher biosafety proved by lower hemolysis probability, stable body weight of mice during the whole experiment and no obvious lesion in histology analysis. Our work provided a useful reference of the formulation of CBZ, which had potential for greater clinical application. Keywords: Cabazitaxel, Liposome, Stability, Apoptosis, Biosafety